Interação entre ergonomia e projeto: o trabalho do operador de descoqueamento em uma refinaria de petróleo - Rodrigues, Daniela da Silva (2012)
This work, developed by a partnership between Ergo&Ação ergonomic group from the Federal University of Sao Carlos and an oil refinery from the state of Sao Paulo, Brazil, has as its primary focus the dialogue between ergonomics and design in the face of a decoking operator work situation. The origin of this demand is related to the occurrence of accidents that happened in the coking unit of the refinery, specifically during the decoking operation. To contribute to the understanding of the determinants and conditioning factors and the mechanisms of this operation, we attempted to systematize the actions of the operators and use their perceptions in the development of the design process. The theoretical background for this work was based on the social process of design, on the Ergonomic Workplace Analysis method (EWA), that is aligned with the corporative guidelines and standards of Health, Safety and Environment of the refinery, and on the Future Activity Approach. The results show two distinct rationales that guide designers of the refinery in the development of conceptual design processes of the company. The interaction between ergonomics and design in the conceptual designs favored the collective construction, enabling ergonomics to act as a member that integrates the conflict of values, representing the various actors in this process.